Artificial Intelligence and Curriculum Implementation of Post-Basic Education and Career Development (PBECD) in Nigeria - Niyi Jacob Ogunode; Ejike, Chinwendu Nneka (Journal of Innovation in Education and Social Research, 2023)
This paper discussed the application of AI in curriculum Implementation of Post-Basic Education and Career Development (PBECD) schools. The paper concluded that AI aids effective school management, lesson presentation, improve learning engagement, assists in conduct of examinations, aids online teaching and learning, aids effective classroom management, aids fast marking and result preparation and aids effective school security. Based on this findings, the paper hereby recommended full integration of AI for management and curriculum implementation of Post-Basic Education and Career Development (PBECD) schools in Nigeria.